Արտատեր Պառավի կերպարը «Սասնա ծռեր» էպոսում - Ղարիբյան, Ալինա (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Фигура старухи имеет в эпосе «Сасна црер» довольно богатый набор мотивов и функций, проявляясь во всех его четырех ветвях. Образ Артатер Парав (хозяйки поля-старухи) выделяется в третьей ветви эпоса устойчивыми мотивами и важной ролью. По своему отношению к полевым работам, а также по другим признакам эта фигура имеет сходство с богинями Деметрой и Анаит, кельтской богиней Старухой-Матерью Тайтиун и знаменитой Старухой Гекалес в греческой мифологии. В эпосе «Сасна црер» Артатер Парав характеризуется многообразием функций, проявляется как в образе женщины с жизненным опытом, так и в образе заботливой матери, а также имеет общие черты с поучающей старухой из сказки. Старуха – персонаж Старой Матери, которая подталкивает Дaвида к испытаниям на пути от юности к зрелости, от невежества к осознанию ответственности. Образ Артатер Парав, как и ряд ее параллелей, включает в себя характеристики почвы, земли, растительности, плодородия, а во взаимоотношениях с богатырским Младенцем она представляет характеристики исполнителя обряда освящения, а также матери-наставницы или приемной матери. Старуха также является той, кто верит в божественную, небесную силу героя и освящает его. В «Сасна црер» Артатер Парав подчинена эпическим диктатам эпоса, эпическим формам характеристики, функций и конечной цели героя, действующего в третьей ветви. Исключительная роль Артатер Парав в третьей ветви эпоса показывает связь Старухи с культовыми слоями земли. The figure of an old woman in the epic “Sasna Tsrer” has a rather rich set of motifs and functions manifesting itself in all four branches of the epic. The image of Artater Parav (the mistress of the field - the old woman) stands out in the third branch of the epic with stable motifs and an important role. In her attitude to field work, as well as in other ways, this figure resembles the goddesses Demeter and Anahit, the Celtic goddess Old Mother Taitiun and the famous Old Woman Hecales in Greek mythology. In the epic "Sasna Tsrer", the image of Artater Parav has an interesting development and is characterized by a variety of functions. She manifests herself both in the image of a woman with life experience and in the image of a caring mother; she has common features with the instructive old woman from the fairy tale. The old woman is an Old- Mother character who pushes David through purification tests on the way from youth to maturity, from ignorance to awareness of responsibility. The image of Artater Parav, as well as a number of her parallels, includes the characteristics of soil, land, vegetation, fertility, while in her relationship with the heroic Infant, she represents the characteristics of the performer of the rite of consecration, as well as the mother-mentor or foster mother. The old woman is also the one who believes in the divine, heavenly power of the hero and sanctifies him. In the epic “Sasna Tsrer”, Artater Parav is subject to the plot dictates of the epic, the epic forms of characterization, the functions and the final goal of the hero acting in the third branch. The exclusive role of Artater Parav in the third branch of the epic shows the connection of the Old Woman with the cult layers of the earth.
Keywords: Բանասիրություն